PENDEKATAN DALAM PENELITIAN LINGUISTIK KEBUDAYAAN - Sabon Ola, Simon (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
ABSTRACT Cultural linguistics is interdisipliner scientific field as interaction between linguistica and culturology. Both linguistics and cultural studies have distinctive characters, in both philosophy substance and its methodology. This article contains methodolical characteristic description, particularly in concerning with the approach applied in cultural linguistics research. The approaches mentioned consist of structural, semiotic, hermeneutic and phenomenologies, ethic and emic, and ethnographic and discourse approaches. The available approaches are relevant with cultural linguistic concept as analysis of co-variative between language structures and users of cultural structure.